PERAN EDITOR DALAM MENGELOLA KONTEN INSTAGRAM @MAINKEBOGORDOTCOM PT. POJOKSATU INDONESIA : PERAN EDITOR DALAM MENGELOLA KONTEN INSTAGRAM @MAINKEBOGORDOTCOM PT. POJOKSATU INDONESIA - Naura Vania Ramadhani (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2026)
This study aims to analyze the implementation of the editor's role in managing the Instagram account reels@mainkebogordotcom at PT Pojok Satu Indonesia. In the modern era with the increasingly advanced development of social media, interaction between humans requires intermediary media. One social media application that is quite well-known to the public is Instagram. Video itself is a form of technology in capturing images and sound directly and processed so that it can be enjoyed repeatedly (Rahmadani, 2020). Video as one of the popular information media is 'Instagram'. The research method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, documentation, and literature studies. The results show that the content creator division plays an active role in the entire creative process from collecting activity data, content planning, visual and narrative content production, to evaluating content performance through Instagram insights. This implementation reflects the practice of a modern editing style that is adaptive to digital transformation, and makes a positive contribution to increasing transparency and public trust in the company